Utilization of didactic material for teaching science and technology concepts in children - Julio Enrique Duarte, Maria Aidé Angarita Velandia, Flavio Humberto Fernández Morales, (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This paper deals with the influence of didactic material, specially designed to study science and technology concepts in the primary level of education. The child preconcepts about science and technology were recopiled by a questionary, after that, the material was applied using a methodology that allows the interaction between students and prototypes, then, a new test was performed to detect changes induced by the pedagogical strategy employed in the classroom. The study was done at five schools in Duitama, Boyacá. As the main result of this research we have the high percentage of students that changed their erroneous conception about the items under study.